Sales lead management in manufacturer-dealer context - Hakanen, Vilma (My University, 2019)
Sales lead management considers all the actions taken to convert suspects into profitable customers. Previous studies have recognized that sales lead management is a simple concept, but companies are struggling with the implementation of effective lead management practices. For example, companies are commonly lacking efficient IT tools to manage sales leads effectively. Additionally, companies are failing to share sufficient information between responsible parties. This study explores sales lead management in a context where products are delivered to B2B customers through sales channel partners. Furthermore, the aim is to explore factors that are critical for the sales lead management success in a manufacturer-dealer context. This qualitative single case study focuses on online inquiries submitted on case company’s website. Theoretical framework is build based on sales process and customer acquisition models and theories. In the empirical part of the thesis, sales lead management is studied from manufacturer’s and dealers’ perspectives to formulate a comprehensive idea of the sales lead process and other critical factors affecting on the sales lead management. The data for the study was collected by interviewing people who are involved in the sales lead management. Through a content data analysis, the study identified sales lead management process phases in manufacturer-dealer context. The phases are similar to the phases the previous literature has recognized. Critical factors are divided into two groups: Success factors and barriers to success. The success factors include high-quality leads and good customer service, whereas barriers for success were identified being prospect and product related factors but also poor customer service. As a theoretical contribution the study expands the existing ideas of sales lead management.
Keywords: Sales lead; sales lead management; manufacturer-dealer context; business to business; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|